Germination of White and Red Quinoa Seeds: Improvement of Nutritional and Functional Quality of Flours - Guardianelli, Luciano Martin (2022)
Quinoa is an Andean grain, classified as pseudocereal and the exploitation of its nutritional profile is of great interest for the cereal-based industry. The germination of quinoa seeds (white and red royal) was tested at 20 °C for different times (0, 18, 24 and 48 h) to select the best conditions for improving the nutritional quality of their flours. Changes in proximal composition, total phenolic compounds, antioxidant activity, mineral content, unsaturated fatty acids and essential amino acids profiles of germinated quinoa seeds were determined. In addition, changes in structure and thermal properties of the starch and proteins as consequence of germination process were analyzed. In white quinoa, germination produced an increase in the content of lipids and total dietary fiber, at 48 h, the levels of linoleic and α-linolenic acids and antioxidant activity increase, while in red quinoa, the component that was mostly increased was total dietary fiber and, at 24 h, increased the levels of oleic and α-linolenic acids, essential amino acids (Lys, His and Met) and phenolic compounds; in addition, a decrease in the amount of sodium was detected. On the basis of the best nutritional composition, 48 h and 24 h of germination were selected for white and red quinoa seeds, respectively. Two protein bands were mostly observed at 66 kDa and 58 kDa, being in higher proportion in the sprouts. Changes in macrocomponents conformation and thermal properties were observed after germination. Germination was more positive in nutritional improvement of white quinoa, while the macromolecules (proteins and starch) of red quinoa presented greater structural changes. Therefore, germination of both quinoa seeds (48 h-white quinoa and 24 h-red quinoa) improves the nutritional value of flours producing the structural changes of proteins and starch necessary for obtaining high quality breads.